2021
DOI: 10.1186/s12902-021-00745-2
|View full text |Cite
|
Sign up to set email alerts
|

Association of serum uric acid levels with COVID-19 severity

Abstract: Aims Hyperuricemia has attracted increasing attention. However, limited concern has been paid to the potential dangers of lowering serum uric acid (SUA). We observed lower levels of SUA in patients with COVID-19. Therefore, we aim to explore whether patients with COVID-19 had SUA lower than normal and the relationship of SUA and the severity of COVID-19. Methods This was a case–control study based on 91 cases with COVID-19 and 273 age- and sex-matc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 32 publications
2
24
0
Order By: Relevance
“…This finding is in line with previous studies. In a recent study by Chang et al, 34 low UA levels were linked to an increased risk of trigeminal neuralgia, which is consistent with our findings in acute and chronic herpetic pain. Because patients with HZ are at a high risk of developing PHN, early and effective interventions can help reduce the occurrence of the disease.…”
Section: Discussionsupporting
confidence: 93%
“…This finding is in line with previous studies. In a recent study by Chang et al, 34 low UA levels were linked to an increased risk of trigeminal neuralgia, which is consistent with our findings in acute and chronic herpetic pain. Because patients with HZ are at a high risk of developing PHN, early and effective interventions can help reduce the occurrence of the disease.…”
Section: Discussionsupporting
confidence: 93%
“…These suggest that low uric acid levels may indicate a higher in ammatory status and death risk in patients with COVID-19. Previous studies have shown that serum uric acid levels are lower than normal in patients with COVID-19 [20][21][22][23]. In our analysis, blood uric acid level was found to be an independent prognostic factor on survival in patients lung cancer with COVID-19 patients (p = 0.008).…”
Section: Discussionsupporting
confidence: 54%
“…Fifth, the potential effect of severity (disease activity) in gout could not be assessed (eg, the presence or absence of tophus or flare frequency). Sixth, in the context of reports of a U-shaped relationship between serum urate levels and COVID-19 outcomes, 23 , 24 , 25 we were unable to investigate any effect of serum urate levels on COVID-19 related death, as these data are unavailable in the UK Biobank. Seventh, the medicine prescribing data were single script from general practitioners only; there was no way of ascertaining adherence or whether participants were taking the medication during the COVID-19 pandemic, although we attempted to account for this by only using prescription information from 2019 and 2020.…”
Section: Discussionmentioning
confidence: 97%